A Comprehensive Study On Microbial Activity And Lipids Extraction From Chicken By-Product Waste Via Supercritical Carbon Dioxide For Biodiesel Production - Ilias, Muhammad Khalish Mohammad (2022)
There is an increasing concern on the safe disposal and sustainable utilization of chicken by-product waste to minimize adverse environmental impacts. The disposal of chicken by-product waste into the landfill leads to the release of antibiotics resistant bacteria into the environment. However, chicken by-product waste contains about 50% fat. The presence of the enormous volume of fat content (about 50 wt.%) in the chicken by-product waste indicates that it could be utilized as a potential low-cost feedstock for biodiesel production. In the present study, the supercritical CO2 (scCO2) technology was utilized to sterilize the chicken by-product waste to ensure safe handling for the subsequent processing towards sustainable utilization of the waste byproduct. The presence of bacteria in the chicken by-product waste and their antibiotics susceptibility were identified. The experimental conditions of scCO2 sterilization were optimized based on the inactivation of the antibiotics resistance bacteria in chicken byproduct waste using Response Surface Methodology (RSM). The optimum experimental conditions for the complete inactivation of the antibiotics resistance bacteria in sterilized chicken by-product waste were scCO2 pressure 18 MPa, temperature 60 oC, and treatment time 45 min. The supercritical CO2 (scCO2) extraction is employed to separate lipids from sterilized chicken by-product waste for biodiesel production. The experimental conditions of scCO2 separation were optimized based on the maximum separation lipids from chicken by-product waste using Response Surface Methodology (RSM).